Influence of Silica as an Abrasive on Friction Performance of Polyimide-Matrix Composites. Issue 1 (January 2017) - Xu, X.L.; Lu, X.; Qin, Z.X.; Yang, D.L.
This study investigated the friction performance of polyimide-matrix composites with various silica powder contents of different sizes. The friction tests were performed on a pin-on-disk tester at various velocities, ranging from 30 to 160 km/h. The experimental results indicate a silica powder size of 0.25±0.05 mm, a sample of 4 wt.% SiO2 demonstrated a high friction coefficient and better wear performance as compared to a sample without silica. The influence of silica content and powder size on the friction coefficient is directly related to the friction velocity. At low friction velocity (30–90 km/h), the friction coefficient increases as the SiO2 content increases, but decreases with increasing SiO2 particle size. At high friction velocity (90–160 km/h), the content and particle size of SiO2 have little influence on the friction coefficient. Experimental results indicate that large SiO2 particles can effectively hinder the motion of third body, which is advantageous to the formation of a compact third body and to the protection of the friction surface.